1993
DOI: 10.1183/09031936.93.06040531
|View full text |Cite
|
Sign up to set email alerts
|

Snoring, asthma and sleep disturbance in Britain: a community-based survey

Abstract: A questionnaire was sent to a random sample of adults in eight locations throughout Britain, to investigate the prevalence of snoring, asthma and sleep complaints in community-based British adult. Of the 1,478 respondents (831 females, 647 males; mean +/- SD age 45 +/- 18 yrs), 37% reported snoring at least occasionally, and 11% reported snoring on at least four nights per week (frequent snorers). Frequent snorers reported spending less time asleep at night, falling asleep accidentally during the day more ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Persons with asthma of all ages and body weights snored more often than the controls in a British population 23 (29% vs 9%). In the European Community Health Respiratory Survey, self-reported habitual snoring and apnea were seen significantly more often in persons with asthma versus in controls without asthma (14% vs 9% and 3% vs 1%, respectively), independent of age, body weight, sex, or smoking status.…”
Section: Epidemiologymentioning
confidence: 97%
“…Persons with asthma of all ages and body weights snored more often than the controls in a British population 23 (29% vs 9%). In the European Community Health Respiratory Survey, self-reported habitual snoring and apnea were seen significantly more often in persons with asthma versus in controls without asthma (14% vs 9% and 3% vs 1%, respectively), independent of age, body weight, sex, or smoking status.…”
Section: Epidemiologymentioning
confidence: 97%
“…Snoring is a very common problem. In a postal survey in the UK, Fitzpatrick et al (1993) found 37% of 1478 respondents described themselves as occasional snorers, and 11% as frequent snorers, snoring at least four nights a week. By the age of 60, snoring affects up to 60% of men and 40% of women (Fairbanks 1991, Norton et al 1993.…”
Section: Introductionmentioning
confidence: 99%